Phylogenetics and systematics of Angiostrongylus lungworms and related taxa (Nematoda: Metastrongyloidea) inferred from the nuclear small subunit (SSU) ribosomal DNA sequences. Issue 3 (13th March 2014) - Eamsobhana, P.; Lim, P.E.; Yong, H.S.
Abstract: The Angiostrongylus lungworms are of public health and veterinary concern in many countries. At the family level, the Angiostrongylus lungworms have been included in the family Angiostrongylidae or the family Metastrongylidae. The present study was undertaken to determine the usefulness and suitability of the nuclear 18S (small subunit, SSU) rDNA sequences for differentiating various taxa of the genus Angiostrongylus, as well as to determine the systematics and phylogenetic relationship of Angiostrongylus species and other metastrongyloid taxa. This study revealed six 18S (SSU) haplotypes in A. cantonensis, indicating considerable genetic diversity. The uncorrected pairwise 'p' distances among A. cantonensis ranged from 0 to 0.86%. The 18S (SSU) rDNA sequences unequivocally distinguished the five Angiostrongylus species, confirmed the close relationship of A. cantonensis and A. malaysiensis and that of A. costaricensis and A. dujardini, and were consistent with the family status of Angiostrongylidae and Metastrongylidae. In all cases, the congeneric metastrongyloid species clustered together. There was no supporting evidence to include the genus Skrjabingylus as a member of Metastrongylidae. The genera Aelurostrongylus and Didelphostrongylus were not recovered with Angiostrongylus, indicating polyphyly of the Angiostrongylidae. Of the currently recognized families of Metastrongyloidea, only Crenosomatidae appeared to be monophyletic. In view of the unsettled questions regarding the phylogenetic relationships of various taxa of the metastrongyloid worms, further analyses using more markers and more taxa are warranted.